DOP48 Hedgehog signalling controls Th17 differentiation to drive intestinal inflammation and is a druggable target for the treatment of IBD. (21st January 2022) - Hanna, J; Beke, F; O'Brien, L; Kapeni, C; Chen, H C; Carbonaro, V; Kim, A; Kishore, K; Adolph, T E; Skjoedt, M O; Skjoedt, K; de la Roche, M; et al.
Abstract: Background: T helper 17 (Th17) cells play an important role in barrier protection in the gastrointestinal tract but are also key pathological drivers of Inflammatory Bowel Disease (IBD). Although a number of transcription factors governing Th17 differentiation have been identified, the intracellular signalling pathways regulating Th17 differentiation are poorly understood. Hedgehog (Hh) signalling controls cell-fate choices in numerous tissue compartments and is targetable by highly selective, clinically-approved small molecule inhibitors. However the role of Hh signalling in Th17 differentiation and effector function is unstudied. Methods: We generated two conditional knockout mouse models targeting Hh signalling components Smo and Ihh to study Th17 differentiation in vitro by flow cytometry and gene expression analysis. For in vivo studies, T cell adoptive transfer colitis was performed using donor Ihh knockout T cells or heterozygote controls. Histological analysis, mouse weight, colon length/weight measurements, and flow cytometric analysis was performed. We supplement this with the use of two small-molecule Smo antagonists for in vitro and in vivo studies of Th17 function. To underscore the translational relevance of our findings, we conducted bioinformatic analyses of published gene expression datasets of human rectal biopsies from two large independent cohorts of Ulcerative Colitis patients and healthy controls. Results: We find that intracellular Hh signalling, independently of extracellular Hh ligands, selectively drives differentiation and effector function of Th17 cells but not of other T helper cell lineages. We demonstrate in vivo that inhibition of the Hh pathway with either the clinically-approved small molecule inhibitor vismodegib or genetic ablation of Ihh in CD4 + T cells results in a significant decrease in histological and clinical readouts of disease severity as well as a significant reduction in IL-17a+ Th17 cells. Our bioinformatic analyses show that Hh component expression levels are upregulated in human Ulcerative Colitis patient samples and are closely correlated with expression of Th17 markers. Mechanistically we show that the T-cell-intrinsic Indian Hedgehog (Ihh) ligand signals via the signal transducer Smoothened to activate both canonical and non-canonical Hh pathways, through the Gli3 transcription factor and AMPK phosphorylation, respectively. Conclusion: We uncover Hh signalling as a novel pathway controlling Th17 differentiation and pathogenicity in IBD with Gli3 acting as a newly-identified crucial regulatory transcription factor. Our work paves the way for the use of Hh inhibitors for the treatment of IBD.